Prospective associations between grandiose narcissism and perfectionism: A longitudinal study in adolescence. (18th January 2023) - Vecchione, Michele; Vacca, Mariacarolina; Dentale, Francesco; Spagnolo, Giorgia; Lombardo, Caterina; Geukes, Katharina; Back, Mitja D.
Abstract: The current study investigates the longitudinal association between grandiose narcissism and multidimensional perfectionism over 2 years in adolescence. We adopted the Narcissistic Admiration and Rivalry Concept, which differentiates between two aspects of grandiose narcissism. We also considered multiple dimensions of perfectionism, including Socially Prescribed Perfectionism (SPP) and two forms of Self‐Oriented Perfectionism (SOP), namely the tendencies to set high standards of performance (SOP‐Striving) and to engage in overly critical self‐evaluations (SOP‐Critical). The study was conducted in a sample of Italian high school students ( n = 331). Concurrent correlations indicated that Admiration was positively related to SOP‐Striving and, to a lesser extent, to SOP‐Critical and SPP. Rivalry was also positively related to the three perfectionistic dimensions, although correlations were smaller in size than those found for Admiration. Prospective associations between narcissism and perfectionism were analysed using a Random‐Intercept Cross‐Lagged Panel Model. Results showed that the predominant direction of effects was from narcissism to perfectionism, particularly from Admiration to SOP‐Striving and SPP. Findings were discussed in terms of their implications for the understanding of the narcissism‐perfectionism link.